Robert Schumann: Herald of a "New poetic age" - Daverio, John (New York Oxford university press, 1997)
Forced by a hand injury to abandon a career as a pianist, Robert Schumann went on to become one of the world's great composers. Among many works, his Spring Symphony (1841), Piano Concerto in A Minor (1841/1845), and the Third, or Rhenish, Symphony (1850) exemplify his infusion of classical forms with intense, personal emotion. His musical influence continues today and has inspired many other famous composers in the century since his death. Indeed Brahms, in a letter of January 1873, wrote: "The remembrance of Schumann is sacred to me. I will always take this noble pure artist as my model."Now, in Robert Schumann: Herald of a "New Poetic Age," John Daverio presents the first comprehensive study of the composer's life and works to appear in nearly a century. Long regarded as a quintessentially romantic figure, Schumann also has been portrayed as a profoundly tragic one: a composer who began his career as a genius and ended it as a mere talent. Daverio takes issue with this Schumann myth, arguing instead that the composer's entire creative life was guided by the desire to imbue music with the intellectual substance of literature. A close analysis of the interdependence among Schumann's activities as reader, diarist, critic, and musician reveals the depth of his literary sensibility. Drawing on documents only recently brought to light, the author also provides a fresh outlook on the relationship between Schumann's mental illness--which brought on an extended sanitarium stay and eventual death in 1856--and his musical creativity. Schumann's character as man and artist thus emerges in all its complexity. The book concludes with an analysis of the late works and a postlude on Schumann's influence on successors from Brahms to Berg.This well-researched study of Schumann interprets the composer's creative legacy in the context of his life and times, combining nineteenth-century cultural and intellectual history with a fascinating analysis of the works themselves.